Plant stress and proteomics in medicinal plants - Kazemi Oskuei, Bita; Masi, Antonio; Kosmala, Arkadiusz; Mahna, Nasser (Frontiers in Plant Science, 2025)
Medicinal plants serve as abundant reservoirs of natural compounds, including pigments, spices, insect repellents, and therapeutic compounds, which are utilized extensively in traditional systems. However, their phytochemicals, potential health benefits, and even response to extreme environments are not fully explored. A range of omics technologies has been extensively utilized in the study of medicinal plants to explore gene functions, unravel biosynthetic pathways of bioactive compounds, and understand the regulatory mechanisms behind gene expression. Due to the complex genetic regulatory network in medicinal plants, new technologies such as proteome assays make it easier to explain biological phenomena. Proteomics could offer a paradigm shift in our understanding of medicinal plants’ cellular metabolism. Until now, few classifications regarding recent and upcoming trends in proteomic studies in medicinal plants have been presented. This review highlights the most recent advances in medicinal plants’ proteomics and how proteomics gains insight into the dynamic changes in medicinal plants’ cellular metabolism.